Understanding the Formation of Heartwood in Larch Using Synchrotron Infrared Imaging Combined With Multivariate Analysis and Atomic Force Microscope Infrared Spectroscopy - Piqueras, Sara; Füchtner, Sophie; Rocha de Oliveira, Rodrigo; Gómez-Sánchez, Adrián; Jelavić, Stanislav; Keplinger, Tobias; de Juan, Anna; Thygesen, Lisbeth Garbrecht (Frontiers in Plant Science, 2020)
Formation of extractive-rich heartwood is a process in live trees that make both them and the wood obtained from them more resistant to fungal degradation. Despite the importance of this natural mechanism, little is known about the deposition pathways and cellular level distribution of extractives. Here we follow heartwood formation in Larix gmelinii var Japonica by use of synchrotron infrared images analysed by the unmixing method Multivariate Curve Resolution – Alternating Least Squares (MCR-ALS). A subset of the specimens was also analysed using atomic force microscopy infrared spectroscopy. The main spectral changes observed in the transition zone when going from sapwood to heartwood was a decrease in the intensity of a peak at approximately 1660 cm-1 and an increase in a peak at approximately 1640 cm-1. There are several possible interpretations of this observation. One possibility that is supported by the MCR-ALS unmixing is that heartwood formation in larch is a type II or Juglans-type of heartwood formation, where phenolic precursors to extractives accumulate in the sapwood rays. They are then oxidized and/or condensed in the transition zone and spread to the neighboring cells in the heartwood.